Corporate Social Responsibility of Chemical Companies in Slovakia - Tetřevová, Liběna (My University, 2018)
The paper deals with the issue of web-based communication of corporate social responsibility activities by chemical companies operating in one of the post-communist countries – Slovakia.
Společenská odpovědnost chemických firem na Slovensku
Keywords: corporate social responsibility; CSR web-based communication; chemical companies; Slovakia; společenská odpovědnost firem; CSR web komunikování; chemické firmy; Slovensko